Pharmacokinetics and safety of deferasirox in subjects with chronic kidney disease undergoing haemodialysis - Maker, G.; Siva, B.; Batty, Kevin; Trengove, R.; Ferrari, P.; Olynyk, John (Wiley-Blackwell Publishing Asia, 2013)
AIM: Treatment of chronic kidney disease (CKD) includes parenteral iron therapy, and these infusions can lead to iron overload. Secondary iron overload is typically treated with iron chelators, of which deferasirox is one of the most promising. However, it has not been studied in patients with CKD and iron overload.METHODS: A pilot study was conducted to evaluate the pharmacokinetics and safety of deferasirox in eight haemodialysis-dependent patients, who were receiving intravenous iron for treatment of anaemia of CKD. Deferasirox was administered at two doses (10 mg/kg and 15 mg/kg), either acute (once daily for 2 days) or steady-state (once daily for 2 weeks).RESULTS: A dose of 10 mg/kg in either protocol was not sufficient to achieve a plasma concentration in the therapeutic range (acute peak 14.1 and steady-state 22.8 mmol/L), while 15 mg/kg in either protocol maintained plasma concentration well above this range (acute peak 216 and steady-state 171 mmol/L). Plasma concentration observed at 15 mg/kg was well above that expected for this dose (40–50 mmol/L), although no adverse clinical events were observed.CONCLUSION: This study highlights the need to profile drugs such as deferasirox in specific patient groups, such as those with CKD and iron overload.